Detection of propranolol in pharmaceutical formulations by diffuse reflectance spectroscopy - Gotardo, Mara Andreia [UNESP]; Tognolli, Joao Olimpio [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
This paper describes an analytical reflectometric method that has an objective not only the industrial quality control but also to detect possible falsifications and/or adulterations of propranolol in pharmaceutical formulations. The method is based on the diffuse reflectance measurements of the colored product (III) of the spot test reaction between propranolol hydrochloride (I) and 2,6-dichloroquinone-4-chloroimide (II) using filter paper as solid support. Spot test conditions have been investigated using experimental design in order to identify and optimize the critical factors. The factors evaluated were DCQ concentration, propranolol solvent and DCQ solvent. The best reaction conditions were achieved with the addition of 30 mu L, of propranolol solution in ethanol 35% (v/v) and 30 mu L of DCQ solution at 70 mg mL(-1) in acetone, in this order. All reflectance measurements were carried out at 500 nm and the linear range was from 8.45 x 10(-4) to 8.45 x 10(-2) mol L-1 (r= 0.998). The limit of detection was 1.01 x 10(-4) mol L-1. No interference was observed from the assessed excipients and drugs. The method was applied to determine propranolol in commercial brands of pharmaceuticals. The results obtained by the proposed method were favorably compared with those given by the British Pharmacopoeia procedure. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: diffuse reflectance spectroscopy; propranolol; spot test; 2,6-dichloroquinone-4-chloroimide; experimental design